Developing productive thinking of a mentally retarded child - Tiambeng, Lourdes Cornelia Lazarte 1946- (College of Education, University of the Philippines Diliman, 1977)
This study was designed to find out the effectivity of a training program in developing creativity of a mentally retarded girl. The 16 year old subject underwent a training program in which she was given lessons in developing observation skills, applying principles in making changes, and other creative exercises for six days. The post test scores and relative percent of change in the Figural Form B of the Torrance Tests of Creative Thinking revealed an increase in all the four creative dimensions with marked increments in elaboration and originality. The writer recommended that further investigation and studies be done on this topic.